Kejadian Depresi pada Lansia di Posyandu Lansia RW I Pagesangan Surabaya - Ika Larasati Sugeng (Journal of Ners and Midwifery, 2016)
Depression in elderly is a problem wich commonly following defect of health status in elderly. Elderly failure of role change, health status, and loss has to be aware. Since it will be the trigger of depression toward elderly. The aim of this study was to indentify the depression case in elderly in POSYANDU LANSIA of RW I Pagesangan Surabaya. The research was descriptive study, with 60 elderly as samples which joined as member of its program. The results showed 29 people (48.3%) were not depressed, 22 people (36.7%) were light depressed, and 9 people (15%) were mid depressed. Several elderly said that no one of their family care of them anymore. So they feel lonely and useless. The elderly who can adapted well to their changes of role, phycis, psychological, and environment would be able to solve their stress and would not be on the depression situation. The correlation of stress and depression was involved by social supports which could be used by the elderly to maintain face the stressors.